The effect of air pollution on morbidity and mortality among children aged under five in sub-Saharan Africa: Systematic review and meta-analysis - Eyasu Alem Lake; Joshua Karras; Guy B. Marks; Christine T. Cowie (PLoS ONE, 2025)
Background Air pollution from indoor and outdoor sources constitutes a substantial health risk to young children in sub-Saharan Africa (SSA). Although some systematic reviews have assessed air pollution and children’s respiratory health in SSA, none have considered both ambient and indoor exposures. Methods This systematic review and meta-analysis assessed the effect of air pollution (ambient and indoor) on respiratory hospitalization and mortality among children under five years in SSA. We retrieved relevant articles from PubMed, Embase, Scopus, African Journals Online (AJOL), Web of Science, and medRxiv. The protocol was registered with Prospero (CRD42023470010). We used guidelines from the preferred reporting items for systematic review and meta-analysis (PRISMA-2020) to guide the systematic review process. Risk of bias was assessed using the Office of Health Assessment and Translation (OHAT) quality appraisal tool. For exposures where there were sufficient studies/data we conducted meta-analyses using random effects models and used Stata version 17 software for analysis. Results For the systematic review we screened 5619 titles and abstracts, reviewed 315 full texts, and included 31 articles involving 2,178,487 participants. Eleven studies examined exposure to solid fuel use in households and its association with all-cause mortality, while four studies explored the impact of passive smoking on mortality among children under five. Only two studies assessed ambient air pollution's effects on all-cause and respiratory-related mortality. Additionally, 13 studies reported varying associations between respiratory hospitalization and household tobacco smoke exposure. Meta-analyses on studies of solid fuel use and mortality and passive smoking and hospitalizations showed that children exposed to indoor solid fuels combustion had higher odds of mortality compared to non-exposed children (OR = 1.31; 95% CI: 1.16–1.47). The meta-analysis of exposure to second-hand smoke found an increased risk of respiratory hospitalization due to pneumonia, although the results were not significant (OR = 1.29; 95% CI: 0.45–3.68), and our certainty of evidence assessment indicated insufficient support to conclusively establish this association. Conclusion and Recommendation Our review reveals that solid fuel use and ambient PM2.5 exposure were associated with increased mortality risk in children under five years in SSA. The meta-analysis showed evidence of an increased risk of under-five years mortality associated with solid fuel use in households. Associations between secondhand smoke and pneumonia hospitalization were less clear. We conclude that significant research gaps remain in understanding the impact of discrete sources of air pollution on the causation of respiratory illness in young children living in SSA. Prioritizing interventions targeting indoor sources is essential, along with further studies which use standardized and objective exposure and outcome measures to study these associations.